Groundwater quality and associated health risks in the Eastern Region of Ghana - Thomas Acquah; Miriam Appiah-Brempong; Geophrey Kwame Anornu (Heliyon)
In the Eastern Region of Ghana, 95 % of residents have access to boreholes. However, approximately 30 % of these boreholes are characterized by unpleasurable taste, odour, oily scum and particulate matter. Thus, this study aimed to assess water quality, predict the sources of groundwater contaminants, evaluate the human health risk and to generate spatial distribution and health risk maps. In achieving this, the water quality of 136 boreholes in the region was evaluated through Water Quality Index (WQI) and Groundwater Pollution Index (GPI) analyses. Multivariate statistical procedures, namely, principal component and correlation analyses were employed to define the major groundwater pollutants and their possible sources. Non-carcinogenic health risk to infants, children and adults through nitrates, iron, manganese and fluorides ingestion was also assessed. The results revealed that groundwater in the region is generally slightly acidic with a mean pH of 6.30. WQI analysis grouped 68 % of the groundwater samples under the ‘excellent’ and ‘good’ water types with the remaining percent categorized under ‘poor’, ‘very poor’ and ‘unsafe’ drinking water types. GPI analysis classified 95 %, 2.21 % and 2.79 % of the boreholes as ‘insignificant’, ‘low’ and ‘highly’ polluted zones. From the multivariate analyses, the dominant pollutants were iron, manganese, chlorides, sodium, fluorides, potassium, turbidity, total suspended and dissolved solids, hardness, alkalinity, sulphates, nitrates and phosphates. The sources of these contaminants are primarily from rock-water interactions and fertilizers. Health risk assessment for nitrates, fluorides, iron and manganese ingestion revealed that 23, 17 and 15 boreholes in the region are likely to pose non-carcinogenic health risk to infants, children and adults respectively. Health risk maps indicated that the most vulnerable districts were Atiwa East, Fanteakwa North, Achiase, Birim South, Akwapim, Suhum and Ayensuano. From these findings, it is imperative that appropriate groundwater remediation measures are implemented in the region to protect public health.